2020
DOI: 10.3390/rs12233973
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of the Hydrological Trends Using Synergistic Approaches of Remote Sensing and Model Evaluations over Global Arid and Semi-Arid Regions

Abstract: Drylands cover about 40% of the world’s land area and support two billion people, most of them living in developing countries that are at risk due to land degradation. Over the last few decades, there has been warming, with an escalation of drought and rapid population growth. This will further intensify the risk of desertification, which will seriously affect the local ecological environment, food security and people’s lives. The goal of this research is to analyze the hydrological and land cover characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 93 publications
0
5
0
Order By: Relevance
“…Under the BWh climate, the mean annual precipitation levels are normally >18 mm, and evapotranspiration is low during summer (June and July) and rarely occurs during spring and winter 99 . In this study, cities that are found under BWh climate are Doha (Qatar), Al‐Kut (Iraq), Ouargla (Algeria), Ghardaia (Algeria), and Khartoum (Sudan) (refer to Table 2).…”
Section: Indoor Thermal Comfortmentioning
confidence: 78%
See 2 more Smart Citations
“…Under the BWh climate, the mean annual precipitation levels are normally >18 mm, and evapotranspiration is low during summer (June and July) and rarely occurs during spring and winter 99 . In this study, cities that are found under BWh climate are Doha (Qatar), Al‐Kut (Iraq), Ouargla (Algeria), Ghardaia (Algeria), and Khartoum (Sudan) (refer to Table 2).…”
Section: Indoor Thermal Comfortmentioning
confidence: 78%
“…Under the BWh climate, the mean annual precipitation levels are normally >18 mm, and evapotranspiration is low during summer (June and July) and rarely occurs during spring and winter. 99 In this study, cities that are found under BWh climate are Doha (Qatar), Al-Kut (Iraq), Ouargla (Algeria), Ghardaia (Algeria), and Khartoum (Sudan) (refer to Table 2). In Doha (Qatar), living rooms built with PCM tiles in an environment with a high ambient temperature (32.8 C-43.0 C), and intense solar radiation levels of 841 W/m 2 were studied.…”
Section: Hot Desert Climate (Bwh)mentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, agriculture in arid lands generally uses crops which are more adapted or resistant to drought (Ihsan et al., 2016), expanding and using smart irrigation systems (Romdhane et al., 2020; Yu et al., 2021), using fertilizers (Dar et al., 2021), changing tillage practices (Shemdoe et al., 2009), and using transgenic genotypes (de la Pena & Pueyo, 2012). However, food production in many drylands globally has been significantly affected by aridification and desertification, which is especially problematic in regions such as the African continent where human populations still show high rates of growth (Elagib, 2014; Li et al., 2020). Predicted shifts from temperate to subtropical drylands, including changes such as the loss of temperature‐controlled seasonal cycles, phenological shifts, increases in frost‐intolerant species, and the dominance of C4 over C3 grasses, may render the cultivation of certain crop species economically unviable in some areas (Schlaepfer et al., 2017).…”
Section: Impacts Of Reduced Water Availability and Soil Fertility On ...mentioning
confidence: 99%
“…However, food production in many drylands globally has been significantly affected by aridification and desertification, which is especially problematic in regions such as the African continent where human populations still show high rates of growth (Elagib, 2014;Li et al, 2020). Predicted shifts from temperate to subtropical drylands, including changes such as the loss of temperature-controlled seasonal cycles, phenological shifts, increases in frost-intolerant species, and the dominance of C4 over C3 grasses, may render the cultivation of certain crop species economically unviable in some areas (Schlaepfer et al, 2017).…”
Section: Impac Ts Of Reduced Water Avail Ab Ilit Y and Soil Fertilit ...mentioning
confidence: 99%